Protein and glycan molecular weight determination of highly glycosylated HIV-1 envelope trimers by HPSEC-MALS. Issue 28 (23rd June 2021) - Bender, Michael F.; Li, Yile; Ivleva, Vera B.; Gowetski, Daniel B.; Paula Lei, Q.
Abstract: High Performance Size-Exclusion Chromatography coupled with Multi-Angle Light Scattering detection (HPSEC-MALS) is an important tool to provide a reliable molecular weight measurement for a large complex biomolecule. A recent HIV-1 soluble envelope trimer vaccine candidate, BG505 DS-SOSIP.664, is among the most glycosylated proteins to enter a clinical trial to date, and determination of its protein and glycan molecular weight is one of the key attributes in pre-clinical characterization. However, protein and glycans possess disparate d n d c values making molecular weight measurement inaccurate in conventional SEC-MALS. To overcome these challenges, a simple mathematically guided experiment was explored, and a composite d n d c value was established by utilizing protein and glycan mass contributions for the HIV-1 envelope trimer. This establishment was further verified by an orthogonal mass spectrometry analysis. This innovative, simple, and quick analytical approach can be applied broadly to measuring the molecular weight of various composite molecular structures, such as complex glycoconjugates.